HISTORICAL CLASSIFICATION AND EFFICIENCY OF THE SUPERVISORY SYSTEM OF INTERNATIONAL LABOR ORGANIZATION - SEVGI, HUSEYIN (Innovare Journal of Social Sciences, 2021)
Objective: International Labor Organization (ILO) has established some supervisory systems to check the extent to which its decisions are implemented. With these supervisory systems, the organization tries to determine to what extent its decisions are implemented by the member countries. In this context, this study aims to classify the types of ILO supervisory systems and to analyze how they work and how effective they are. Methods: This study is based on a systematic literature review. Rather than the traditional literature review, a systematic literature review implies that efficient, systematic, and reproducible methods to identify, evaluate, and synthesize existing literature. As the basis of the literature review, ScienceDirect databases have been selected. 239 research articles and 23 book chapters were analyzed. Results: When we examine the supervisory mechanisms in the ILO, one point should be emphasized to fully grasp the topic as a whole and to define the impact of the organization in today’s global capitalist system: ILO is an international organization with no concrete sanction power despite its many supervisory systems. Conclusions: The main reason for the lack of sanction tools in the ILO’s control system lies in its ideological background. As a representative of the reformist ideology, the ILO aims to impose its rules on the states by “persuasion method” as required by this ideology.